Successful breeding of a flightless female Eagle Owl Bubo bubo. (1st November 2016) - Milchev, Boyan; Gruychev, Gradimir
A flightless female Eagle Owl Bubo bubo has survived for one year with food provided by its partner. The pair bred successfully and raised one owlet in 2015. The favourable combination of characteristics on the rocky slope nest site occupied by the pair provided the female different escape routes from potential enemies, natural protection of the nest and access to water during the time of laying, incubation period and hot summer weather. Voles (Microtus sp.) were the most numerous prey (55.8% by number, 15.3% by biomass) because of their population spike during the period with a flightless female in the pair. Rats (Rattus sp.; 16.2% by number, 31.2% by biomass), a key prey resource, also increased to a level several times greater than in previous years. The significant differences in diet during 2015 did not appear to cause any obvious changes in Eagle Owl breeding characteristics at the site. The increasing prey on voles and rats created the narrowest food niche and reduced food stress according to the rather lower value of superpredation (3.6% by number, 9.9% by biomass).